2015
DOI: 10.1126/scitranslmed.aac6336
|View full text |Cite
|
Sign up to set email alerts
|

Development of a therapeutic monoclonal antibody that targets secreted fatty acid–binding protein aP2 to treat type 2 diabetes

Abstract: The lipid chaperone aP2/FABP4 has been implicated in the pathology of many immunometabolic diseases, including diabetes in humans, but aP2 has not yet been targeted for therapeutic applications. aP2 is not only an intracellular protein but also an active adipokine that contributes to hyperglycemia by promoting hepatic gluconeogenesis and interfering with peripheral insulin action. Serum aP2 levels are markedly elevated in mouse and human obesity and strongly correlate with metabolic complications. These observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 62 publications
0
74
0
2
Order By: Relevance
“…9 Furthermore, a recent study demonstrated the possibility of a new strategy to treat metabolic disease by targeting serum FABP4 with a monoclonal antibody. 10 Circulating FABP4 may directly promote the progression of atherosclerosis in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Furthermore, a recent study demonstrated the possibility of a new strategy to treat metabolic disease by targeting serum FABP4 with a monoclonal antibody. 10 Circulating FABP4 may directly promote the progression of atherosclerosis in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study demonstrated the possibility of a new strategy to treat metabolic disease by targeting serum FABP4 with a monoclonal antibody to FABP4. 10 Elevated circulating FABP4 levels are associated with obesity, IR, T2DM, hypertension, dyslipidemia, cardiac dysfunction, renal dysfunction, atherosclerosis and cardiovascular events. 6,11-18 Notably, an increased plasma level of FABP4 was shown to be independently associated with the presence of coronary artery disease.…”
mentioning
confidence: 99%
“…Mechanistically, secreted FABP4 has been demonstrated to increase liver glucose production and insulin secretion and decrease cardiomyocyte contractility (59,200,201), and hence, may explain some of the detrimental effects of uncontrolled lipolysis. These effects of circulating FABP4 support the possibility of using neutralizing antibodies to treat metabolic disease, and this approach has proven successful in preclinical models (59,202,203).…”
Section: Therapeutic Potential Of Targeting Inflammatory Lipids In Mementioning
confidence: 99%
“…1417 Moreover, animal experiments have shown that FABP4, when expressed in macrophages, contributes particularly to the etiology of atherosclerosis. 18,19 In addition, epidemiological data supported a positive association between circulating FABP4 levels and the risk of T2D, heart failure, and stroke in the general population.…”
Section: Introductionmentioning
confidence: 99%